2016
DOI: 10.1016/s0140-6736(16)00620-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical workload in UK primary care: a retrospective analysis of 100 million consultations in England, 2007–14

Abstract: SummaryBackgroundPrimary care is the main source of health care in many health systems, including the UK National Health Service (NHS), but few objective data exist for the volume and nature of primary care activity. With rising concerns that NHS primary care workload has increased substantially, we aimed to assess the direct clinical workload of general practitioners (GPs) and practice nurses in primary care in the UK.MethodsWe did a retrospective analysis of GP and nurse consultations of non-temporary patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
477
8
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(508 citation statements)
references
References 7 publications
18
477
8
5
Order By: Relevance
“…9,12,13,18,19 A recently published quantitative study using the Clinical Practice Research Datalink (CPRD) found a 12% rise in GP consultation rates between 2007-2008 and 2013-2014, and an increase in the duration of consultations, contributing to an overall workload increase of 16%. 20 A British Medical Association focus group identified similar issues to those highlighted here, including a shift in care provision from secondary to primary care, increasing patient expectations and demands (with some GPs practising defensively), too much bureaucracy, and partnership being unattractive due to high workload and responsibility. 16 An online GP survey reported that 82% of participants intended to leave general practice, take a career break, and/or reduce clinical hours in the next 5 years, primarily due to workload intensity.…”
Section: Comparison With Existing Literaturementioning
confidence: 64%
“…9,12,13,18,19 A recently published quantitative study using the Clinical Practice Research Datalink (CPRD) found a 12% rise in GP consultation rates between 2007-2008 and 2013-2014, and an increase in the duration of consultations, contributing to an overall workload increase of 16%. 20 A British Medical Association focus group identified similar issues to those highlighted here, including a shift in care provision from secondary to primary care, increasing patient expectations and demands (with some GPs practising defensively), too much bureaucracy, and partnership being unattractive due to high workload and responsibility. 16 An online GP survey reported that 82% of participants intended to leave general practice, take a career break, and/or reduce clinical hours in the next 5 years, primarily due to workload intensity.…”
Section: Comparison With Existing Literaturementioning
confidence: 64%
“…3 Workload for GPs has increased by 16% in the past 7 years, 4 while less than one in five UK Foundation Year 2 doctors went into general practice in 2015. 5 The patient population is growing faster than the GP workforce, with rising demands due to an ageing population and increase in multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The specific types of training for HCPs that the experts thought would be most helpful and that HCPs would be most likely to actually participate in were individualized training in their offices and a clear and concise tutorial provided in the DHT itself. These results suggest that strategies that are most convenient and time-efficient, particularly given the ever increasing workload demands that HCPs encounter [34], are likely to be most feasible and effective for HCPs.…”
Section: Resources and Training For Hcps And Patientsmentioning
confidence: 91%